Coal Dust Characteristics and Its Association with Air Quality in Palembang Coal Unloading Station - Arie Wahyudi; Hilda Zulkifli; Susila Arita; Rico Januar Sitorus (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2022)
The problem of coal dust due to the accumulation and loading of coal to barges for shipping has not been studied optimally. This study aimed to investigate the characteristics of coal dust and the air quality of the three coal industries. Coal dust characteristics were tested through proximate analysis, XRD, XRF, and SEM. Meanwhile, air quality is viewed from exposure to gases that cause emissions (CO, NO2, and SO2), PM10 and TSP, humidity, and temperature. Coal dust consists of SiO2, Al2O3, and Fe2O3 as the main components with high ash. Exposure to SO2 and TSP can potentially exceed the annual threshold value.